STRATEGIC GUIDANCE AND COUNSELING INTERVENTIONS TO OVERCOME LEARNING BARRIERS, A CASE STUDY AT SMP NEGERI 178 JAKARTA - Susilowati Susilowati; Ahmad Suryadi (Multidisciplinary Research Studies in Social Sciences, 2025)
Learning difficulties remain a persistent and multifaceted challenge among junior high school students, significantly impacting academic achievement, motivation, and classroom engagement. This study explores the strategic implementation of guidance and counseling (GC) services in addressing these issues at SMP Negeri 178 Jakarta. Utilizing a qualitative case study design, data were gathered through observation, in-depth interviews, and document analysis. Findings indicate that GC services are systematically delivered through individual and group counseling sessions, classroom-based interventions, and motivational enhancement programs. The primary learning issues identified include diminished motivation, academic anxiety, inadequate study skills, and socio-emotional challenges that hinder student performance. Effective GC service delivery is supported by strong collaboration among counselors, subject teachers, homeroom teachers, and parents, alongside institutional support from school leadership. Conversely, barriers such as limited counselor availability, low student engagement, and a lack of awareness regarding the function of GC services impede optimal outcomes. The study concludes that the effectiveness of GC interventions is contingent upon contextually responsive, personalized, and collaborative approaches. These findings underscore the need to strengthen policy, enhance counselor professional development, and integrate GC programs into the school’s educational management system.Keywords: Guidance and Counseling; Learning Challenges; Individual Counseling; School Collaboration; Secondary Education